In order to solve for the variable in the equation Mikel first applies the distributive property. Which equation is a result of this step?
![In order to solve for the variable in the equation Mikel first applies the distributive property Which equation is a result of this step class=](https://us-static.z-dn.net/files/d5f/97f510ae2eaccff4287317b742585a96.jpg)
Answer:
1 - x - 2 + 2x = 10x - 25 - x
Step-by-step explanation:
We have the expression: 1 - (x+2) + 2x = 5(2x - 5) - x
Applying the distributive property we get:
1 - x - 2 + 2x = 10x - 25 - x
So, the following equation is the result of that step: 1 - x - 2 + 2x = 10x - 25 - x
Answer:
The equation is:
[tex]1-x-2 + 2x = 10x-25-x[/tex]
Step-by-step explanation:
The distributive property says that
[tex]c(a+b) = ac + bc[/tex]
In this case we have the following equation
[tex]1-(x+2) + 2x = 5(2x-5)-x[/tex]
Then apply the distributive property as shown below
[tex]1-1*x-1*2 + 2x = 5*2x-5*5-x[/tex]
Now simplify the expression
[tex]1-x-2 + 2x = 10x-25-x[/tex]
So the equation that results after applying the distributive property is:
[tex]1-x-2 + 2x = 10x-25-x[/tex]